SUSTAINABILITY PERFORMANCE USING ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) SCORES: EVIDENCE FROM PUBLIC LISTED COMPANIES (PLCS) IN MALAYSIA - Norashikin Ismai1; Mohamad Azwan Md Isa; Nor Hadaliza Abd. Rahman; Nurul Farhana Mazlan (International Journal of Accounting, Finance and Business, 2020)
Malaysia shows the highest sustainability disclosure rate (64.5%) among the fiveASEAN countries followed by Singapore (61.7%), Thailand (60%), the Philippines (56.3%) andIndonesia (53.6%). Based on the KPMG’s Survey of Corporate Reporting 2017, 97% of top100 Malaysian PLCs have published their sustainability performance compared to the worldaverage of 72%. This reveals that Malaysian PLCs are concerned on the importance ofsustainability reporting and sustainability performance. Therefore, this study aims to assess thesustainability performance in relation to financial performance. This study also examinesfactors influencing the sustainability performance. A sample of 39 PLCs from ten industriesover 2010 to 2018 are chosen in this study. The sustainability performance is measured by ESGscore, which is obtained from Thomson Reuters. This study has four independent variables,namely firm size, leverage, profitability and economic performance. Pearson correlation andmultiple regression tests are conducted to meet the objectives of study. The findings show thatprofitability and size of company have positive and significant impact towards the sustainabilityperformance. Also, the sustainability reporting has an influence on the company financialperformance. Essentially, this study bridges the knowledge gap of establishing a relationshipbetween sustainability with firm performance considering three pillars of sustainability, namelyenvironmental, social and governance.